What really drove Silicon Valley and First Republic Bank Bankruptcy? - Guillen, Jorge (2024)
This paper analyses the possible determinants that induced Silicon Valley and First Republic Bank to Bankruptcy. We employ financial statements for a sample of Banks in line with the business core of Silicon Valley Bank. The period under assessment ranges from 2006-2022. We estimate an indicator of Bank Efficiency using the technique Data Envelopment Analysis (DEA). The latter indicator is used as the primary step to analyze failure within sample banks. According to the CAMEL model, macroeconomic variables are non-significant but relevant variables that drive failure were: Bank Efficiency, Capital adequacy, Earning ability, and Liquidity position ratio. Our study is relevant for any policy making to prevent any future bank failure.